Chromosomes studies in Orchidaceae from Argentina - Daviña, Julio Rubén (2009)
The center of diversity of Argentinean orchids is in the northeast region of the country. Chromosome numbers and karyotype features of 43 species belonging to 28 genera are presented here. Five chromosome records are the first ones at the genus level; these taxa are Aspidogyne kuckzinskii (2n = 42), Eurystyles actinosophila (2n = 56), Skeptrostachys paraguayensis (2n = 46), Stigmatosema polyaden (2n = 40) and Zygostates alleniana (2n = 54). In addition, a chromosome number is presented for the first time for 15 species: Corymborkis flava (2n = 56), Cyclopogon callophyllus (2n = 28), C. oliganthus (2n = 64), Cyrtopodium hatschbachii (2n = 46), C. palmifrons (2n = 46), Galeandra beyrichii (2n = 54), Habenaria bractescens (2n = 44), Oncidium edwallii (2n = 42), O. fimbriatum (2n = 56), O. pubes (2n = 84), O. riograndense (2n = 56), Pelexia ekmanii (2n = 46), P. lindmanii (2n = 46) and Warrea warreana (2n = 48). For Oncidium longicornu (2n = 42), O. divaricatum (2n = 56) and Sarcoglottis fasciculata (2n = 46+1B?, 46+3B?), a new cytotype was found. Chromosome data support phylogenetic relationships proposed by previous cytological, morphologic and molecular analyses, and in all the cases cover some gaps in the South American literature on orchid chromosomes.